The Role of Host-Generated H2S in Microbial Pathogenesis: New Perspectives on Tuberculosis - Rahman, Md. Aejazur; Glasgow, Joel N.; Nadeem, Sajid; Reddy, Vineel P.; Sevalkar, Ritesh R.; Lancaster, Jack R.; Steyn, Adrie J. C. (Frontiers in Cellular and Infection Microbiology, 2020)
For centuries, hydrogen sulfide (H2S) was considered primarily as a poisonous gas and environmental hazard. However, with the discovery of prokaryotic and eukaryotic enzymes for H2S production, breakdown, and utilization, H2S has emerged as an important signaling molecule in a wide range of physiological and pathological processes. Hence, H2S is considered a gasotransmitter along with nitric oxide (•NO) and carbon monoxide (CO). Surprisingly, despite having overlapping functions with •NO and CO, the role of host H2S in microbial pathogenesis is understudied and represents a gap in our knowledge. Given the numerous reports that followed the discovery of •NO and CO and their respective roles in microbial pathogenesis, we anticipate a rapid increase in studies that further define the importance of H2S in microbial pathogenesis, which may lead to new virulence paradigms. Therefore, this review provides an overview of sulfide chemistry, enzymatic production of H2S, and the importance of H2S in metabolism and immunity in response to microbial pathogens. We then describe our current understanding of the role of host-derived H2S in tuberculosis (TB) disease, including its influences on host immunity and bioenergetics, and on Mycobacterium tuberculosis (Mtb) growth and survival. Finally, this review discusses the utility of H2S-donor compounds, inhibitors of H2S-producing enzymes, and their potential clinical significance.